Building Automation Systems as Tool to Improve the Resilience from Energy Behavior Approach. (2015) - Osma, German; Amado, Laura; Villamizar, Rodolfo; Ordoñez, Gabriel
Abstract: This paper shows how the building automation systems (BAS) are a powerful tool for companies face some permanent or temporary changes that can occur in the surrounding environment, which can affect the welfare of users, increase the energy consumption and/or demand more financial investment to strengthen or to replace the actual systems to attend the needs of users. However, these systems not properly used because of designers and owners ignore the specific qualities of these and the designs lacks of scenario analysis. The automation systems can monitor several variables in real time and analyze historical data to adjust quickly the operation of the devices to provide comfort of users and integrity of devices; this capacity keeps the core purpose in the face of changed circumstances. Also, this work shows how would be the potential behavior of two buildings considering some changes in their environment for specific tropical conditions, one of them with automation system and the other without this system; for that, we made first the characterization of a BAS implemented in a building in Bucaramanga (Colombia) and after specific simulations. The changes considered are heat island, energy outages, new construction and new habits of users.